KARAKTERISTIK TEPUNG BERAS HASIL PERLAKUAN KOMBINASI GELOMBANG MIKRO, ULTRASONIKASI DAN PEMANASAN LEMBAB - Shinta Dewi Ardhiyanti; Adil Basuki Ahza; Didah Nur Faridah; Bram Kusbiantoro (Jurnal Teknologi dan Industri Pangan, 2016)
Broken and brewer rice as by product of rice milling can be developed into a functional product with higher economic value, i.e. higher resistant starch (RS) rice flour. This research was aimed to study the modification of broken and brewer rice flour by the combination of microwave and ultrasonication with heat moisture treatment (HMT) to enhance RS contents and its associated microstructural and pasting characteristics changes. The results showed that five modified rice flours that had the highest RS contents were ultrasonicated with 20% of moisture content-HMT 10 and 12 hours rice flours, microwaved with 20% of moisture content-HMT 10 hours rice flour, microwaved with 50% of moisture content-HMT 8 and 10 hours rice flours. Their RS content ranged from 6.50–9.25% which were higher than the RS content of native rice flour (1.89%). Those five modified flours showed noticeable structural changes from the disappearance of non starch particulates, becoming more porous and larger size matrices. The pasting temperature of those modified flour increased (0.11–9.16% from native flour’s pasting temperature) and their peak viscosity decreased (47.15–71.15% from native flour’s peak viscosity). The modified flour had improved heat stability with the decrease in breakdown (88.07–100.00% from native flour’s breakdown value) and less retrogradation tendency during cooling (44.38–66.62% from native flour’s setback value). The combined treatment caused reduction of crystalinity ratio from 0.94 (native) to 0.91-0.86 (modified flour).